Public expenditure management and financial accountability in Niger. (World Bank country study., 2005)
"Effective, efficient, and transparent management of public resources is particularly important in a poor country like Niger. This study shows how difficult it is for Niger to significantly change its expenditure composition in a short time span. A narrow and volatile domestic resource base, heavy dependence on aid, and a large share of pre-determined expenditures, such as external debt payments, are important factors behind this lack of flexibility. There are ways, though, to create space in the budget for increasing public spending on priority sectors. The study identifies a number of measures in this regard, such as increasing domestic revenues, more realistic and conservative budgeting, strengthening cash management, controlling the wage bill, borrowing prudently, and attracting higher external financing for recurrent costs in priority sectors."